Chaetomiaceae Fungi, Novel Pathogens of Equine Neurotropic Phaeohyphomycosis. (September 2017) - Plumlee, Quinci; Meason-Smith, Courtney; Dieterly, Alexandra; Gomez, Gabriel; Porter, Brian F.; Rodrigues Hoffmann, Aline
Many previously unrecognized fungi are emerging as potential pathogens. One such group is dematiaceous fungi of the Chaetomiaceae family (phylum Ascomycota, class Sordariomycetes). These fungi are rare causes of opportunistic, neurotropic phaeohyphomycosis in humans but are not known to cause similar infections in animals. The aims of this study were to investigate equine hyphal mycotic encephalitis, characterize key histopathologic features, and classify causative organisms with molecular diagnostic techniques. Seven cases were evaluated by histopathology. Panfungal PCR targeting the ribosomal RNA large subunit coding region and the noncoding internal transcribed spacer-2 region was performed on DNA extracted from formalin-fixed, paraffin-embedded sections of affected brain, and the resulting sequences were queried against published fungal genomes. Affected animals ranged from 8 to 22 years of age and presented with neurologic signs. Macroscopic lesions within affected brains included multifocal hemorrhage, focal swelling of the thalamus with red and yellow discoloration, and focal cerebral malacia. Major histologic findings included multifocal discrete foci of necrosis, neutrophilic to granulomatous inflammation, vasculitis, and intralesional fungal hyphae variably affecting the cerebrum, thalamus, and brainstem. DNA sequences in 4 cases showed > 98% homology with species within the Chaetomiaceae family, including Acrophialophora fusispora, Acrophialophora levis, and Chaetomium strumarium . Histomorphologically, Chaetomiaceae fungi were 7 to 10 μm wide, septate, parallel walled, and nonpigmented, with dichotomous branching in affected horses. This case series is the first report of equine mycotic encephalitis caused by members of the Chaetomiaceae family, previously reported as rare emerging pathogens in humans.